Effectiveness of Therapeutic Education Program on Self Efficacy and Self Care Behavior among Patients with Type II Diabetes Mellitus at Selected Hospitals in Chennai - Tamilarasi, B. (Innovational: Journal of Nursing and Healthcare, 2024)
Background: Diabetes mellitus is a syndrome of disturbed energy metabolism, conventionally defined by the degree of hyperglycemia, resulting from an absolute or relative deficiency of insulin action. Objectives: This study is to evaluate the effectiveness of the therapeutic education program on self-efficacy and self-care behavior among patients with type II diabetes mellitus at selected hospitals in Chennai. Methods: A pre-experimental, one group pre-test and post-test research design was used, and 30 patients with type II diabetes mellitus who met inclusion criteria were selected using the purposive sampling technique. The level of self-efficacy and self-care behavior measured using the diabetes management self-efficacy scale and the summary of diabetes self-care activities, respectively. The post-test was done on 7th day using same tool after the therapeutic education program. Results: Mean score for self-efficacy in the pre-test was 57.57 with a standard deviation of 10.36, and in the post-test it was 76.23 with a standard deviation of 16.97. The difference in self-efficacy between the pre-test and post-test levels was highly statistically significant (P < 0.05) at 4.93 for the paired t-value. In terms of self-care behavior, the pre-test mean score was 35.03 with a standard deviation of 6.56, and the post-test mean score was 62.47 with a standard deviation of 9.76. There was a very statistically significant difference (P < 0.05) between the pre-test and post-test levels of self-care behavior, as indicated by the paired t value of 12.33*. Conclusion: Patients with type 2 diabetes mellitus benefit from therapeutic education programs in terms of self-care behavior and self-efficacy.